2010
DOI: 10.1177/0145721710366758
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of a Web-Based Intervention on Psychosocial Well-Being Among Adults Aged 60 and Older With Diabetes

Abstract: These findings provide support for the conclusion that a Web-based intervention is effective in improving the psychosocial well-being of participants at a 6-month follow-up. Future research needs to investigate the long-term effectiveness of Web-based interventions for sustaining psychosocial well-being, including factors that may affect quality of life, such as diabetes-specific beliefs, attitudes, social support, and disease-specific coping skills.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
156
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 111 publications
(159 citation statements)
references
References 44 publications
1
156
0
2
Order By: Relevance
“…According to these criteria, a total of five studies were identified [21,[30][31][32][33]. A summary of the reviewed articles is provided in Table 1.…”
Section: Methods Data Source and Inclusion Criteriamentioning
confidence: 99%
See 4 more Smart Citations
“…According to these criteria, a total of five studies were identified [21,[30][31][32][33]. A summary of the reviewed articles is provided in Table 1.…”
Section: Methods Data Source and Inclusion Criteriamentioning
confidence: 99%
“…Three studies had waitlist as control [21,30,31], one added daily emotion reporting [31]. One study used treatment as usual as control [33].…”
Section: Studies Designmentioning
confidence: 99%
See 3 more Smart Citations